PEMIKIRAN SAYYID MUHAMMAD AL-MALIKI TERHADAP MOTIF CHILDFREE GENERASI Z - Enri Auni, Ayfa Fayzayil (Universitas Nurul Jadid, 2024)
The childfree decision is certainly motivated by a variety of motives. This paper aims to understand the motives for generation Z's childfree decision and analyze Sayyid Muhammad bin Alawi Al-Maliki's thoughts on generation Z's childfree motives through the mafhum muwafaqah method. This research was conducted through a field study with a descriptive analysis approach. The results of this study reveal that the decision not to have children (childfree) is not only limited to married couples, but is also found among the unmarried generation Z. The motivations underlying this decision vary, as they are the same as those of the married couple.The motivations underlying this decision vary and include personal concerns, traumatic experiences and health conditions such as schizophrenia. With the results of analyzing Sayyid Muhammad's thoughts using the mafhum muwafaqah method, the motive for the decision to go childfree without being based on real specific emergency reasons is unacceptable and unjustified.The childfree decision is certainly motivated by a variety of motives. This paper aims to understand the motives for generation Z's childfree decision and analyze Sayyid Muhammad bin Alawi Al-Maliki's thoughts on generation Z's childfree motives through the mafhu>m muwa>faqah method. This research was conducted through a field study with a descriptive analysis approach. The results of this study reveal that the decision not to have children (childfree) is not only limited to married couples, but is also found among the unmarried generation Z. The motivations underlying this decision vary, as they are the same as those of the married couple.The motivations underlying this decision vary and include personal concerns, traumatic experiences and health conditions such as schizophrenia. With the results of analyzing Sayyid Muhammad's thoughts using the mafhu>m muwa>faqah method, the motive for the decision to go childfree without being based on real specific emergency reasons is unacceptable and unjustified.